International educational migration as a “soft power resource” in the globalization era - V. A. Suvorova; I. A. Bronnikov (Управление)
The international educational migration as a resource of «soft power» of the state has been analyzed in the article. Based on comprehensive analysis of the existing definitions of educational migration the author’s interpretation of this concept have been proposed. Based on the data of UNESCO, the Institute of international education of the United States, the Ministry of Science and Higher Education of the Russian Federation the statistics of international educational migration has been presented and analyzed. The main emphasis has been made on such categories of international educational migrants as students (bachelors, masters), postgraduate students. The reasons for the popularity of foreign students in countries such as Canada and the United States have been described. Based on the study two groups of factors have been highlighted: external and internal (motivational) factors, influencing decision-making in choosing the country of study.Based on the data of the Ministry of Science and Higher Education of the Russian Federation, the advantages of education in Russia have been analyzed. The issue of adaptation of foreign students in Russian universities has been considered: first-year curatorial programs, the Institute of student fellowships. It has been concluded hat Russian universities have a wealth of experience in teaching and adaptation of foreign students.The concepts and projects to attract foreign students to the Russian Federation also have been described in detail. Special attention to two projects “5–100” and “Export of Russian education” has been paid. The Federal Agency for the Commonwealth of Independent States Affairs, Compatriots Living Abroad, and International Humanitarian Cooperation (Rossotrudnichestvo) as one of the main institutions in the export of Russian education has been designated. The measures to attract foreign students to Russian universities have been proposed.